Nurses' use of social media during the COVID-19 pandemic-A scoping review. - Stinne Glasdam; Helena Sandberg; Sigrid Stjernswärd; Frode F Jacobsen; Anette H Grønning; Lisbeth Hybholt (PLoS ONE)
Background During the COVID-19 pandemic, nurses stand in an unknown situation while facing continuous news feeds. Social media is a ubiquitous tool to gain and share reliable knowledge and experiences regarding COVID-19. The article aims to explore how nurses use social media in relation to the COVID-19 pandemic. Method A scoping review inspired by Arksey and O'Mally was conducted by searches in Medline, CINAHL, Academic Search Complete and Web of Sciences. Empirical research studies investigating nurses' use of social media in relation to COVID-19 were included. Exclusion criteria were: Literature reviews, articles in languages other than English, articles about E-health, and articles investigating healthcare professionals without specification of nurses included. Articles, published in January-November 2020, were included and analysed through a thematic analysis. The PRISMA-ScR checklist was used. Results Most of the eleven included studies were cross-sectional surveys, conducted in developing countries, and had neither social media nor nurses as their main focus of interest. Three themes were identified: 'Social media as a knowledge node', 'Social media functioned as profession-promoting channels' and 'Social media as a disciplinary tool'. Nurses used social media as channels to gain and share information about COVID-19, and to support each other by highlighting the need for training and changes in delivery of care and redeployment. Further, social media functioned as profession-promoting channels partly sharing heroic self-representations and acknowledgment of frontline persons in the pandemic, partly by displaying critical working conditions. Finally, nurses used social media to educate people to perform the 'right 'COVID-19' behaviours in society. Conclusion This review provided snapshots of nurses' uses of social media from various regions in the world, but revealed a need for studies from further countries and continents. The study calls for further multi-methodological and in depth qualitative research, including theoretically framed studies, with a specific focus on the uses of social media among nurses during the pandemic.